Effects of stretch shortening cycle exercise fatigue on stress fracture injury risk during landing - James, C. R.; Dufek, J. S.; Bates, B. T. (Research Quarterly for Exercise and Sport, 2006)
The purpose of this study was to examine changes in landing performance during fatigue that could result in increased stress fracture injury risk. Five participants performed nonfatigued and fatigued drop landings (0.60 m), while ground reaction force (GRF), electromyographic (EMG) activity, and kinematics were recorded. Fatigue was defined as a 5-20% reduction in vertical jumping performance. Single-subject analyses revealed that all participants were affected (p < .05) by fatigue. Post hoc comparisons revealed a group effect (p < .05) for selected variables. Participants landed with (a) less joint flexion at contact and used a greater range of motion, (b) greater GRF peaks and loading rates, and (c) less EMG activity. These changes were consistent with greater risk of stress fracture.